Measuring the impact of plant breeding on sub-Saharan African staple crops - Eriksson, D.; Akoroda, M.; Azmach, G.; Labuschagne, Maryke T.; Mahungu, N.; Ortíz, R. (SAGE Publications, 2018)
Many countries in sub-Saharan Africa (SSA) are facing huge challenges regarding food insecurity, low agricultural output, and agriculturally incurred environmental degradation. A sustainable and increased crop productivity and diversity is essential to achieve food security in a socially, economically, and environmentally sustainable way. Plant breeding is an important factor contributing to the increased crop productivity and diversity, giving farmers access to genetically improved cultivars that yield more, have better resistance to biotic and abiotic stresses, and meet consumer expectations. To motivate and encourage further investments, it is important to measure the actual impact of breeding. This review considers available research on the impact of breeding through yield gain and of food security, focusing on 10 important staple crops in SSA. The overall impression is that breeding produces a very high return on investment. Such investments remain centerpieces for meeting the challenges in this region. The discussion focuses on the most important future breeding priorities for each crop, the actors involved, and the importance of mechanisms for dissemination and farmer adoption, and concludes with some policy recommendations.